Implementation of the Child-Friendly Education Unit (SRA) Program to Improve the Quality of Education at Islamic Senior High Schools in Tarakan City - Muhammad Tauhid (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the implementation of the Child-Friendly Education Unit (SRA) Program and its implications for improving the quality of education at Madrasah Aliyah (Islamic Senior High School) in Tarakan City. The study used a qualitative approach, with data collection techniques including interviews, observation, and documentation. The results indicate that the implementation of the SRA Program is carried out through management functions, including planning, organizing, implementing, and monitoring. This program is realized through the development of child-friendly policies, the development of safe and inclusive learning, the prevention of violence and bullying, the provision of supportive infrastructure, and the strengthening of student and parent participation. The implementation of the SRA has been proven to have positive implications for improving the quality of education, as indicated by the creation of a safe and comfortable learning environment, increased student discipline and character, improved learning processes, and increased participation of all members of the madrasah community in supporting a culture of quality. This study found that the success of SRA implementation is determined not only by meeting program indicators but also by the commitment of all members of the madrasah community to building an educational culture oriented towards protecting and fulfilling children's rights. This is an effective strategy for supporting the improvement of the quality of education at Madrasah Aliyah in Tarakan City.